Analysis of minimally invasive directional antennas for microwave tissue ablation. (2nd January 2017) - Sebek, Jan; Curto, Sergio; Bortel, Radoslav; Prakash, Punit
Abstract: Purpose: Microwave ablation (MWA) applicators capable of creating directional heating patterns offer the potential of simplifying treatment of targets in proximity to critical structures and avoiding the need for piercing the tumour volume. This work reports on improved directional MWA antennas with the objectives of minimising device diameter for percutaneous use (≤ ∼13 gauge) and yielding larger ablation zones. Methods: Two directional MWA antenna designs, with a modified monopole radiating element and spherical and parabolic reflectors are proposed. A 3D-coupled electromagnetic heat transfer with temperature-dependent material properties was implemented to characterise MWA at 40 and 77 W, for 5 and 10 min. Simulations were also used to assess antenna impedance matching within liver, kidney, lung, bone and brain tissue. The two antenna designs were fabricated and experimentally evaluated with ablations in ex vivo tissue at the two power levels and treatment durations ( n  = 5 repetitions for each group). Results: The computed specific absorption rate (SAR) patterns for both antennas were similar, although simulations indicated slightly greater forward penetration for the parabolic antenna. Based on simulations for antennas inserted within different tissues, the proposed antenna design appears to offer good impedance matching for a variety of tissue types. Experiments in ex vivo tissue showed radial ablation depths of 19 ± 0.9 mm in the forward direction for the applicator with spherical reflector and 18.7 ± 0.7 mm for the applicator with parabolic reflector. Conclusion: These results suggest the applicator may be suitable for creating localised directional ablation zones for treating small and medium-sized targets with a percutaneous approach.